Towns in the dark? : urban transformations from late Roman Britain to Anglo-Saxon England - Speed, Gavin (Archaeopress archaeology., 2014)
What became of towns following the official end of 'Roman Britain' at the beginning of the 5th century AD? Did towns fail? Were these ruinous sites really neglected by early Anglo-Saxon settlers and leaders? Developed new archaeologies are starting to offer alternative pictures to the traditional images of urban decay and loss revealing diverse modes of material expression, of usage of space, and of structural change. The focus of this book is to draw together still scattered data to chart and interpret the changing nature of life in towns from the late Roman period through to the mid-Anglo-Saxon period. The research centres on towns that have received sufficient archaeological intervention so that meaningful patterns can be traced.